Event-related brain potential correlates of two states of conscious awareness in memory - Düzel, Emrah (The National Academy of Sciences of the USA, 1997)
We report an event-related potential (ERP) experiment of human recognition memory that explored the relation between conscious awareness and electrophysiological activity of the brain. We recorded ERPs from healthy adults while they made “remember” and “know” recognition judgments about previously seen words. These two kinds of judgments reflect “autonoetic” and “noetic” awareness, respectively. The ERP effects differed between the two kinds of awareness while they were similar for “true” and “false” recognition. Noetic awareness was associated with a temporoparietal positivity in the N400 range (325–600 ms) and a late (600–1,000 ms) frontocentral negativity, whereas autonoetic awareness was associated with a widespread, late, bifrontal and left parietotemporal (600–1000 ms) positivity. In the very late (1,300–1,900 ms) time window, a right frontal positivity was observed for both remember and know judgments of both true and false targets. These results provide physiological evidence for two types of conscious awareness in episodic memory retrieval.